Long‐term suspended sediment and particulate organic carbon yields from the Reynolds Creek Experimental Watershed and Critical Zone Observatory. Issue 2 (17th February 2022) - Glossner, Kayla L.; Lohse, Kathleen A.; Appling, Alison P.; Cram, Zane K.; Murray, Erin; Godsey, Sarah E.; Van Vactor, Steve; McCorkle, Emma P.; Seyfried, Mark S.; Pierson, Fredrick B.
Abstract: Long‐term (>20 y) suspended sediment (SS) and particulate organic carbon (POC) records are relatively rare and yet are necessary for understanding linkages between climate, erosion and carbon export. We estimated long‐term (>23 y) SS and POC yields from four nested catchments that ranged from <1 to 54 km 2 in area across the Reynolds Creek Experimental Watershed and Critical Zone Observatory (RCEW‐CZO) in southwestern Idaho, USA. We found strong relationships between log10 SS and log10 POC (R 2  = 0.38–0.86) that varied across catchments but remained robust across years, one dry and one of the wettest water years on record. Mean annual SS yields varied from 18 to 89 g SS m −2  y −1 and POC from 0.6 to 11.0 g C m −2  y −1 across the four catchments. Water yield explained much of the temporal variation (72%–85%) in SS and POC yields except in a small, snow‐dominated headwater catchment where it explained 15%–51%. The largest five water years accounted for 69%–84% of the total SS and POC yields in catchments with 24 y records. All catchments had positive slopes (>0) for SS and POC concentration‐discharge (C‐Q) relationships, with large catchments exhibiting greater slopes (0.66–0.97) than smaller ones (0.14–0.16). In addition, most catchments were dominated (80%) by clockwise hysteretic curves. Lack of seasonal exhaustion in the SS‐POC relationships, positive C‐Q and clockwise relations indicated that these systems were transport‐rather than supply limited, and that sediment and POC appeared to be sourced from channel/bank erosion and remobilization. POC yields represent 1%–10% of mean water year net ecosystem exchange depending on elevation; lower elevation catchments may shift from being carbon sinks to sources after accounting for fluvial POC export associated with changes in climate. Abstract : This study utilized historic suspended sediment (SS) data alongside contemporary particulate organic carbon (POC) data from the Reynolds Creek Experimental Watershed and Critical Zone Observatory to derive functional relationships capable of hindcasting POC yields over a 23‐year period. We show that mean annual yields range from 20 to 89 g m −2 y −1 and 0.87 to 11.0 g m −2 y −1 for SS and POC, respectively. Our findings indicate that long‐term denudation of SS, but also POC is driven by low frequency, high‐magnitude disturbance events.